2019
DOI: 10.1016/j.ebiom.2019.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Limb-Bud and Heart (LBH) promotes angiogenesis in human glioma via VEGFA-mediated ERK signalling under hypoxia

Abstract: Background: Glioma is the most common primary malignant tumor in the central nervous system with frequent hypoxia and angiogenesis. Limb-Bud and Heart (LBH) is a highly conserved transcription cofactor that participates in embryonic development and tumorigenesis. Methods: The conditioned media from LBH regulated human glioma cell lines and patient-derived glioma stem cells (GSCs) were used to treat the human brain microvessel endothelial cells (hBMECs). The function of LBH on angiogenesis were examined through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…Studies have shown that the mechanism of microvessel proliferation and basal membrane degradation in other diseases, such as cancers and strokes, involves the JAK2/ STAT3, IL-6/JAK2/STAT3, and MMP-9 pathways, which regulate the progression of tumor metastasis [9][10][11]. Currently, the pathways involved in hypoxia-mediated microvessel proliferation and basal membrane degradation have not been reported, except the IL-6/JAK2/STAT3/MMP-9 pathway in our study [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the mechanism of microvessel proliferation and basal membrane degradation in other diseases, such as cancers and strokes, involves the JAK2/ STAT3, IL-6/JAK2/STAT3, and MMP-9 pathways, which regulate the progression of tumor metastasis [9][10][11]. Currently, the pathways involved in hypoxia-mediated microvessel proliferation and basal membrane degradation have not been reported, except the IL-6/JAK2/STAT3/MMP-9 pathway in our study [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…With the STAT3 inhibitor, many factors should be analyzed. Firstly, it is well established that regulation of erythropoiesis and vasculogenesis is an adaption to hypoxia in the healthy body [6][7][8][9]. On the one hand, previous studies showed that hematopoietic and endothelial cell lineages share common progenitors that affect the proliferation and differentiation of bone marrow-derived or umbilical cord blood-derived endothelial progenitor cells, which in turn promote angiogenesis [56,57].…”
Section: Ch + Dmso Ch + Inhibitor Ch Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of GCM has been previously described [24]. Briefly, we used serum-free DMEM/F12 to wash GSCs three times, followed by culturing the GSCs for 24 h. The medium was then collected and centrifuged at 3000×g for 15 min at 4°C to remove GSCs and debris.…”
Section: Preparation Of the Glioma Conditioned Medium (Gcm)mentioning
confidence: 99%
“…In atherosclerotic, folic acid reduced atherosclerotic lesion through elevating DNA methyltransferase activity and expression, altering MCP1 and VEGF promoter methylation, and inhibiting MCP1 and VEGF expression [17]. The expression of VEGF was signi cant up-regulated in human glioma via [18,19].…”
Section: Introductionmentioning
confidence: 99%